Synthesis of yttrium-doped barium zirconate and yttrium-doped barium cerate core-shell structure as proton-conducting solid electrolyte for intermediate temperature solid oxide fuel cells - Balanay, Mary Jozen S.
With the growing population, there is an increasing demand in power consumption and attached with it is the need for more energy production. Thus, it is of great importance to seek other forms of energy source aside from the depleting fossil fuels. This is where renewable sources became necessary and one form of this is the clean energy conversion by fuel cells. At present, the use of solid oxide fuel cells (SOFCs) is gaining weight for providing a clean and efficient energy conversion, flexibility in conversion and high fuel utilization (Fergus 2006). It has been known that the use of conventional oxide ion conductors (e.g. Y-doped stabilized zirconia) as solid electrolytes in SOFCs needed high operating temperatures that ranges from 800-1000°C (Kreuer 2003; Kannan et al. 2013). Aside from the high energy needed for the cell operation, material degradation and high costs of metallic interconnects are the major disadvantages faced (Kannan et al. 2013). Many studies are now focusing on the development of ceramic proton conductors as these would address the problem in high temperature operation of SOFCs. Electrolytes of this kind normally operates at intermediate temperatures (400-700°C) (Kannan et al. 2013; Babilo & Haile 2005). The main purpose of this study is to develop an oxide proton conductor and investigate its proton conductivity at intermediate temperature. This thesis synthesizes a proton-conduction ceramic material using wet chemistry method for use as a solid electrolyte at intermediate working temperature